Peramalan Inflow dan Outflow Uang Kartal Menggunakan X-13 ARIMA-SEATS - Herdiantini , Rizka Fitria; Kartikasari, Mujiati Dwi (Jurusan Matematika FMIPA UNM, 2024)
Currency is an important part of Indonesian society's economic transactions. In order to effectively manage the amount of currency in circulation, Bank Indonesia must carefully plan and estimate its currency needs. One way to estimate this need is by looking at Bank Indonesia's inflow and outflow. Therefore, forecasting currency inflow and outflow is crucial for future planning. Inflow and outflow data are included in the time series that is affected by calendar variations. Traditional forecasting methods, such as exponential smoothing and ARIMA, cannot handle these variations. Therefore, this study uses the X-13 ARIMA-SEATS method, which is able to forecast time series data with the effect of calendar variations. Based on monthly data on currency inflow and outflow from January 2015 to December 2022, the results show that the X-13 ARIMA-SEATS method is effective when used with the mean absolute percentage error (MAPE) criteria.